Dynamic relationships between emotional distress, persecutory ideation, and metacognition in schizophrenia. Issue 4 (27th November 2019) - Buck, Benjamin; Gagen, Emily C.; Luther, Lauren; Kukla, Marina; Lysaker, Paul H.
Abstract: Objective: Determine whether metacognitive capacity (i.e., a range of abilities that involve recognition, reflection, and integration of mental states) influences the relationships between emotional distress and persecutory ideation (PI). Methods: The present study examined emotional distress, metacognition and PI in a sample ( n  = 337) of individuals with schizophrenia or schizoaffective disorder and clinician‐rated PI. Pearson and partial correlations were used to examine relationships between variables, as well as between‐subjects analysis of variances to compare groups characterized based on emotional distress and persecutory ideation scores. Results: While emotional distress and PI are associated with one another, metacognition is negatively associated with PI and positively associated with emotional distress. Subgroup comparisons demonstrated that individuals with high emotional distress and low PI had significantly higher metacognitive capacity than those elevated in PI or reduced in both emotional distress and PI. Conclusions: Findings suggest metacognitive capacity may relate to improved awareness of distress and reduced PI.